Chiral Urea-Catalyzed Asymmetric Mannich Reaction of 3-Fluorooxindoles with α-Amidosulfones: Synthesis of Optically Active α-Fluoro-β-amino-oxindoles - Zhang, Xin; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Lin, Yingjie; Duan, Haifeng (Synlett, 2022)
The asymmetric Mannich reaction of 3-fluorooxindoles and α-amidosulfones catalyzed by a chiral urea catalyst derived from quinine in presence of K3PO4 was developed. Through the asymmetric reaction, a series of α-fluoro-β-amino-oxindoles, containing a tertiary carbon stereocenter, could be obtained in high yields (up to 95%) with high enantioselectivity (95%) and diastereoselectivity (>99:1). Such α-fluoro-β-amino-oxindole compounds are expected to become candidates in the field of medicine.
Keywords: Mannich reaction; 3-fluorooxindoles; α-fluoro-β-amino-oxindoles; quinine-derived skeleton; urea-catalyzed catalysts